EFL Teachers and Students’ Views of Using Mendeley as Reference Management Tools in Academic Writing - Jhems Richard Hasan; Alvons Habibie (Eduvelop: Journal of English Education and Development, 2023)
Mendeley as one of the reference managers today is widely used by academics in the process of writing scientific papers. This study aims to explore the perceptions of EFL teachers and students regarding the use of Mendeley as a tool in supporting the process of writing scientific papers. The EFL students involved in this study were 25 final year students of the English Education Department, IAIN Sultan Amai Gorontalo, while there were 15 EFL teachers who were also the subject of this study. Perception data from the two subjects were taken using a self-completion questionnaire and interview guidelines. Perception data was then analyzed descriptively quantitatively and qualitatively. The perceptions of students and lecturers regarding Mendeley as a management reference tool in writing scientific papers can be said to be positive. This is proven by the benefits of Mendeley for writing which is very necessary to support the writing process. Several journals that require articles using Mendeley are also an important point for lecturers in adjusting article templates to the intended journal. This positive implication needs to be followed up as a policy within the English Education Department of IAIN Sultan Amai Gorontalo in the future.